Nurse-led service for children with gastrostomies: a 2-year review. (22nd April 2021) - Patel, Radhika; Mutalib, Mohamed; Pradhan, Akhilesh; Wright, Hannah; Upadhyaya, Manasvi
Abstract : Background: Percutaneous endoscopic gastrostomy (PEG) feeding can provide long-term nutritional support for patients with a functional gastrointestinal system but insufficient oral intake. Some patients, however, may require jejunal feeding, which can be achieved using a PEG tube with jejunal extension (PEG-J). A previous review at a tertiary paediatric hospital revealed poor documentation and a high incidence of buried bumper syndrome (BBS) in children with gastrostomies. Subsequently, a nurse-led service for gastrostomy care was introduced. Aim: To determine the impact of the nurse-led service. Methods: Prospective review, at 1 year and 2 years, following either a PEG or PEG-J insertion. Patient records were reviewed and a telephone survey was conducted. Statistical analysis was performed using Fisher's exact test. Findings: 32 PEG and 6 PEG-J patients were included in this study. There was 100% documentation of provision of care instructions. Average satisfaction with the service was over 8/10. Incidence of BBS was 0% in the PEG group and 17% in the PEG-J group. Of those parents/carers surveyed, 74% wanted additional tube care support via SMS text message. Conclusion: Introduction of a nurse-led service resulted in complete documentation of provision of care and sustained high levels of parental satisfaction. Future care should focus on utilising technological platforms.